Pengembangan Modul Ajar PKn Kurikulum Merdeka di Kelas V Sekolah Dasar - Imron, Meitha Rahmawati; Mivtha Citraningrum; Mustika irianti (STKIP Andi Matappa Pangkep, 2024)
This research is a Research And Development (R&D) research with a 4-D model modified into 3-D, with 3 stages of research, namely Define, Design, and Develop. Class V students of SD Inpres 28 Sorong Regency totaling 26 students are the subjects in this study. The instrument used is a questionnaire to obtain validation results from validators. The results of this study show that the teaching module of the Independent Curriculum Pkn class V with learning unit 1